Cost-effectiveness of Recombinant Zoster Vaccine (RZV) and Varicella Vaccine Live (VVL) against herpes zoster and post-herpetic neuralgia among adults aged 65 and over in Japan. Issue 27 (12th June 2019) - Hoshi, Shu-ling; Seposo, Xerxes; Shono, Aiko; Okubo, Ichiro; Kondo, Masahide
Highlights: Two kinds of vaccine, VVL and RZV, are available for prevention of HZ among adults age ≥50 in Japan. We evaluated the value for money of VVL and RZV vaccination programmes for adults age ≥65 in Japan. Vaccination programs with either vaccine can be cost-effective regardless of the age. Vaccination for 65–84 y.o. with VVL or RZV should only be considered when introducing a programme. Optimal strategy varies between the two vaccines depending on the willingness-to-pay threshold. Abstract: Background: The approval of the extended use of 1-dose varicella vaccine (VVL) in adults aged 50 and older against herpes zoster (HZ) in 2016 and the 2-dose recombinant zoster vaccine (RZV) in 2018 raised the need to evaluate the value for money between these two vaccines. Methods: We conducted a cost-effectiveness analysis with Markov modelling to evaluate the efficiency of the immunisation programmes from payer's perspective. Eight strategies with different ages to receive VVL or RZV were set, namely: 65–84 year old (y.o.), 70–84 y.o., 75–84 y.o., and 80–84 y.o. VVL- or RZV-strategy. Incremental cost-effectiveness ratios (ICERs) compared with curative care scenario were calculated. The health statuses following the target cohort were as follows: acute HZ followed by recovery, post-herpetic neuralgia followed by recovery, post HZ/PHN, recurrence of HZ, and general death. Results: At the vaccination cost ¥8000 (US$73) for 1-dose ZVL and ¥30, 000 (US$273) for 2-dose RZV, ICERs ranged from ¥2, 633, 587/US$23, 942 (age 80–84 y.o.) to ¥3, 434, 267 or US$31, 221 (age 65–84 y.o.)/QALY gained for VVL-strategies; from ¥5, 262, 227 or US$47, 838 (age 80–84 y.o.) to ¥6, 278, 557 or US$57, 078/QALY gained (age 65–84 y.o.) for RZV-strategies. Cost-effectiveness acceptability curves derived from probabilistic sensitivity analyses showed that if the cost-effective threshold was at ¥3, 000, 000 or US$27, 273/QALY, the acceptability was 90.7% and 8.8% for 65–84 VVL-strategy and 65–84 RZV-strategy, respectively; if at ¥5, 000, 000 or US$45, 455/QALY, 56.2% and 43.8%, and if at ¥10, 000, 000 or US$90, 909/QALY 11.9% and 88.1%, respectively. Conclusion: Vaccinating individuals aged 65–84 y.o., 70–84 y.o., 75–84 y.o., 80–84 y.o. with VVL or RZV to prevent HZ-associated disease in Japan can be cost-effective from payer's perspective, with vaccination costs at ¥8, 000 per shot for VVL, ¥30, 000 for 2-dose RZV. While the results suggesting that only 65–84 VVL-strategy and 65–84 RZV strategy should be considered when introducing HZ immunisation programme. The optimal strategy varies depending on the willingness-to-pay threshold.